Histone demethylase JMJD1A in cancer progression and therapeutic resistance. Issue 4 (12th January 2022) - Jeon, Hee‐Young; Ryu, Hyunju; Pornour, Majid; Qi, Jianfei
Abstract: JMJD1A (also called lysine demethylase 3A [KDM3A]) belongs to the Jumonji C family of histone demethylases. It specifically removes the repressive mono‐ or di‐methyl marks from histone H3 at lysine 9 and thus contributes to the activation of gene transcription. JMJD1A plays a key role in a variety of biological processes such as spermatogenesis, metabolism, sex determination, and stem cell activity. JMJD1A is upregulated in various types of cancers and can promote cancer development, progression, and therapeutic resistance. JMJD1A can epigenetically regulate the expression or activity of transcription factors such as c‐Myc, androgen receptor (AR), estrogen receptor (ER), β‐catenin, and so on. Expression and activity of JMJD1A in cancer cells can be regulated at transcriptional, post‐transcriptional, and post‐translational levels. Targeting JMJD1A may repress the oncogenic transcription factors as a potential anticancer therapy.